Analysis of Work-Related Stress and its Effect on Teachers’ Commitment to their Job in Self-Financing Colleges in the Dharmapuri District - S. Savitha; K. Krishna Kumar (Recent Advances in Commerce, Management, and Tourism, 2023)
Teaching is a rewarding but challenging profession, especially in higher education. Most teachers are high achievers who enjoy working hard and are constantly seeking ways to get better. Yet, college teachers face numerous difficulties, such as job-related stress and burnout. College professors’ dedication to their jobs will decline as a result of work-related burnout, which can cause much more than just a general sense of exhaustion or overwhelm. This study examines how work-related burnout affects the work commitment of college teachers employed by self-supporting colleges in the Dharmapuri District of Tamil Nadu State. Descriptive and inferential analyses are performed using a sample of 150 college teachers who work in self-financing colleges. The association between work-related burnout and college teachers’ work commitment is examined using the Independent Sample "t" Test, One-way ANOVA, Correlation, and Multiple Regression. The study discovered that compared to their male counterparts, female college teachers felt increased work-related burnout. College teachers who work in self-financing colleges have highly positive associations between work-related burnout indicators and work commitment. Excessive Stress is the strongest component among the five elements that contribute to burnout at work.